2000
DOI: 10.1007/s11627-000-0070-y
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of plantlets from leaf and petiole explants of Pelargonium x hortorum

Abstract: The in vitro plant regeneration potential of vegetatively propagated geraniums (Pelargonium  hortorum) has been investigated. Using various combinations of growth regulators and a choice of different explants, a regeneration protocol has been developed to raise in vitro plantlets from young petiole and leaf explants from three different cultivars of geraniums. In all three cultivars, very young petiole explants exhibited a higher regeneration potential as compared with leaf explants. Regeneration efficiencies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
1
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 19 publications
1
10
1
1
Order By: Relevance
“…'Frensham' KrishnaRaj et al, 1997or 'Dubonnet' Boase et al, 1996. Exceptions are the studies of Robichon et al (1997) who analysed seven P. peltatum cultivars, of Agarwal and Ranu (2000) with three P. zonale cultivars and that of Haensch (1999) testing thirty-five cultivars from both P. zonale and P. peltatum hybrids. In order to assess the general practicability of the regeneration system for pelargonium breeding, we performed our study with sixteen cultivars of economic importance.…”
Section: Regeneration Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…'Frensham' KrishnaRaj et al, 1997or 'Dubonnet' Boase et al, 1996. Exceptions are the studies of Robichon et al (1997) who analysed seven P. peltatum cultivars, of Agarwal and Ranu (2000) with three P. zonale cultivars and that of Haensch (1999) testing thirty-five cultivars from both P. zonale and P. peltatum hybrids. In order to assess the general practicability of the regeneration system for pelargonium breeding, we performed our study with sixteen cultivars of economic importance.…”
Section: Regeneration Experimentsmentioning
confidence: 99%
“…For practical application, it is strongly recommended that explants can be obtained from adult plants, because the genotypes have to be tested for agronomic performance before using them for transformation, and, moreover the vegetativelypropagated pelargoniums are highly heterozygous resulting in variable offspring. For P. zonale as well as P. peltatum hybrids, a number of reports has been published which dealt with in vitro regeneration from explants taken from adult plants either using organogenesis (Cassells and Carney, 1987;Dunbar and Stephens, 1989;Boase et al, 1996;Robichon et al, 1997;Agarwal and Ranu, 2000;Mithila et al, 2001) or using somatic embryogenesis (Cassells, 1979;Robichon et al, 1997;Haensch, 1999;Mithila et al, 2001). In the case of somatic embryogenesis, the most restricting problem is the applicability of the system, which has been shown to work efficiently for a few model genotypes (KrishnaRaj et al, 1997), but was not transferable to a wider range of genotypes of actual economic importance (Haensch, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Agarwal and Ranu (2000), used mature explants of P. x hortorum and found a higher regeneration ability of petioles compared to leaves. Recently, Nassour and Dorion (2002) found that leaves were the best source for protoplast isolation and plant regeneration from leaf protoplasts of P. x hortorum 'Alain'.…”
Section: Introductionmentioning
confidence: 99%
“…A micropropagação é uma das técnicas de cultura de tecidos que vem sendo bastante empregada para a manutenção de germoplasma, bem como, a propagação comercial de muitas plantas medicinais e aromáticas, com o objetivo de se obter mudas com qualidades agronômicas desejáveis, indexadas, livres de patógenos e com elevado padrão genético, para síntese de metabólitos secundários e/ou produção de óleos essenciais (França, 2004).…”
Section: Introductionunclassified